The Going‐Concern Market Anomaly - KAUSAR, ASAD; TAFFLER, RICHARD J.; TAN, CHRISTINE (Journal of Accounting Research, 2009)
ABSTRACT We explore the market response to announcements of first‐time going‐concern (GC) audit opinions and, for a subset of these cases, their subsequent withdrawal, from 1993 to 2005. We find that the market fully responds to GC withdrawal announcements but underreacts to the GC announcements themselves, resulting in a downward drift of −14% over the one‐year period subsequent to the GC opinion. This result is robust to alternative explanations documented in prior literature. However, after adjusting for transactions costs, the opportunity to earn profits by trading on this market anomaly is limited. We demonstrate that despite such clear adverse signals about the firm's continuing financial viability, this information is not being fully impounded by the market on a timely basis. Our findings differ from those of others who suggest that there is no pricing anomaly associated with GC opinions in the United States. We show that this is likely due to important issues with their research methods.